First note that $T = c^*$ (using regular expression syntax). We can therefore rewrite your grammar to:
S --> c*a | b | Sc
Rewriting even further, we can say that $S = (c^*a | b)c^*$, so $S$ is regular. It is not hard to come up with a grammar for this language:
S --> T a T | b T
T --> c T | λ
More generally, when trying to rewrite grammars to $LL$ form, one first removes left recursion using standard techniques (for instance here). Then one tries to remove any conflicts that are left, for which no general techniques are known - just try to figure out what the conflict means, and try to solve it accordingly.